Effects of the 20 March 2015 solar eclipse in Strasbourg, France. (7th March 2016) - Kastendeuch, Pierre P.; Najjar, Georges; Colin, Jérôme; Luhahe, Raphaël; Bruckmann, Francis
Abstract : On 20 March 2015 a partial solar eclipse occurred at Strasbourg, France, with an obscuration of 72.4%. The consequences of this event were observed under optimal weather conditions with micrometeorological instruments. Among these, the global radiation deficit can be estimated to be of 1.724MJ per horizontal square meter. A modification of the solar spectrum with a greater proportion of photosynthetically active radiation was also observed. The extinction of the solar radiation resulted in a reduction of the net radiation, a sharp decrease in the surface temperatures and a change in all surface heat fluxes.